Surgical Repair of Radial-Ulnar Fracture by Static Intramedullary Interlocking Nailing in a Crossbred Heifer - Narang, Ankit; Singh, Tarunbir; Singh, Simrat S.; Verma, Pallavi; Saini, Narinder S.; Mohindroo, Jitender; Udehiya, Rahul (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective Study included surgical management of radius and ulna fracture in a 2-year-old, 220 kg crossbred heifer presented with a 2-day-old history of injury resulting in severe, non-weight bearing lameness of the left forelimb.Methods The condition was diagnosed clinically and confirmed radiographically as a middle third oblique comminuted fracture of the left radius and ulna. Static intramedullary interlocking nailing was performed for fracture fixation. An interlocking nail of 12-mm diameter and 26-cm length was introduced in a retrograde manner from the distal aspect of the radius.Results The animal was able to bear weight on the affected limb within 7 days post surgery. Good callus formation and complete weight bearing were observed by 35th day. Bending of the screws and osteophytic reaction were the major postoperative complications observed radiographically.Clinical Significance From this case study, it was established that static intramedullary interlocking nailing can be used as an alternative technique for fracture repair of the radius and ulna in cattle where stable fracture fixation by bone plating is questionable.
Keywords: radius ulna; fracture; interlocking nailing; cow